Kinetic Analysis of 2-[C]Thymidine PET Imaging Studies of Malignant Brain Tumors: Preliminary Patient Results - Joanne M. Wells; David A. Mankoff; Janet F. Eary; Alexander M. Spence; Mark Muzi; Finbarr O'Sullivan; Cheryl B. Vernon; Jeanne M. Link; Kenneth A. Krohn (Molecular Imaging)
2-[ 11 C]Thymidine (TdR), a PET tracer for cellular proliferation, may be advantageous for monitoring brain tumor progression and response to therapy. Kinetic analysis of dynamic TdR images was performed to estimate the rate of thymidine transport ( K 1t ) and thymidine flux ( K TdR ) into brain tumors and normal brain. These estimates were compared to MRI and pathologic results. Methods: Twenty patients underwent sequential [ 11 C]CO 2 (major TdR metabolite) and TdR PET studies with arterial blood sampling and metabolite analysis. The data were fitted using the five-compartment model described in the companion article. Results: Comparison of model estimates with clinical and pathologic data shows that K 1t is higher for MRI contrast enhancing tumors ( p > .001), and K TdR increases with tumor grade ( p > .02). On average, TdR retention was lower after treatment in high-grade tumors. The model was able to distinguish between increased thymidine transport due to blood–brain barrier breakdown and increased tracer retention associated with tumor cell proliferation. Conclusion: Initial analysis of model estimates of thymidine retention and transport show good agreement with the clinical and pathological features of a wide range of brain tumors. Ongoing studies will evaluate its role in measuring response to treatment and predicting outcome.